The effects of different prosthetic materials on the formation of collagen types in incisional hernia - Baktir, A.; Dogru, O.; Girgin, M.; Aygen, E.; Kanat, B. H.; Dabak, D. O.; Kuloglu, T. (Springer, 2013)
The aim of this study was to determine the rate of collagen Type I/Type III for different meshes. Fifty rats were used. Five groups were formed: prolene (n = 10), mersilene (n = 10), parietex (n = 10), e PTFE (n = 10) and control group (n = 10). In all animals, laparotomy was performed using a midline incision. After that four different kinds of meshes are placed into the retro-rectus plane and fixed with a non-absorbable suture. Rectus superficial fascia and skin are closed. In the control group, repairment is done primarily. Thirty days later, meshes are found through the incisions that were done previously. Scar tissues above and near by meshes and also in the control group are taken, and in these tissue samples, the ratio of Type I/III is evaluated histochemically. The Prolene mesh was found to contain more collagen fibers than e PTFE. As a result of the histopathologic evaluation, it was seen that Group I contained statistically significantly more collagen density than the other four groups (p < 0.05). Moreover, the collagen Type I/III ratio in the specimen taken from the top part and the surrounding area of Group I was found significantly higher than the collagen Type I/III ratios of the rest of the groups (p < 0.05). As a conclusion, the ratio of collagen Type I/III is the highest in the prolene group.
Keywords: Incisional hernia; Collagen types; Prosthetic materials